MUHAMMADIYAH DA’WAH, SOCIAL CAPITAL, AND MUSLIM COMMUNITY RESILIENCE IN KENDARI - Muhammad Obie; Bakri Yusuf (JURNAL PENELITIAN KEISLAMAN, 2026)
This study aims to analyze the role of Muhammadiyah da’wah as a social practice in building social capital and transforming the resilience of Muslim communities in Kendari City. This research employs a qualitative approach with a case study design, using in-depth interviews, participant observation, and documentation involving Muhammadiyah da’wah actors and community members. The findings reveal that Muhammadiyah da’wah functions not only as an activity of conveying religious teachings but also as a social practice that strengthens networks of trust, collective norms, and social solidarity within the community. Da’wah practices grounded in education, social services, and community empowerment significantly contribute to enhancing the community’s adaptive capacity in facing various social, economic, and cultural pressures. Theoretically, this study highlights the importance of integrating da’wah perspectives with the concept of social capital in understanding the dynamics of Muslim community resilience in urban contexts.